2004
DOI: 10.1038/sj.hdy.6800443
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and differentiation in Eryngium alpinum L. (Apiaceae): comparison of AFLP and microsatellite markers

Abstract: Genetic diversity and structure of 12 populations of Eryngium alpinum L. were investigated using 63 dominant amplified fragment length polymorphism (AFLP) and seven codominant microsatellite (48 alleles) markers. Within-population diversity estimates obtained with both markers were not correlated, but the microsatellite-based fixation index F is was correlated with both AFLP diversity indices (number of polymorphic bands and Nei's expected heterozygosity). Only AFLP diversity indices increased with the size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 53 publications
(64 reference statements)
3
106
1
1
Order By: Relevance
“…So far, only a few, mostly regional studies have included direct comparison between AFLP and microsatellite variation. The results suggest that AFLPs may reveal more structure in large data sets than microsatellites (Gaudeul et al, 2004;Woodhead et al, 2005;S nsteb et al, 2007).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…So far, only a few, mostly regional studies have included direct comparison between AFLP and microsatellite variation. The results suggest that AFLPs may reveal more structure in large data sets than microsatellites (Gaudeul et al, 2004;Woodhead et al, 2005;S nsteb et al, 2007).…”
Section: Introductionmentioning
confidence: 80%
“…Higher intrapopulation genetic diversity could be expected for microsatellites because of their higher mutation rate (Mariette et al, 2001;Gaudeul et al, 2004), but the different measures should be correlated. However, our sampling sizes were small, and selfing populations may show variable genetic diversity depending on the number of lineages sampled.…”
Section: Aflps Versus Microsatellitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, for molecular markers characterized by a higher mutation rate (SSRs compared with AFLPs), there were no (or only very small) differences in the diversities observed in the two main geographical areas, whereas there was much lower diversity in the Andes for AFLPs compared with the Mesoamerican wild P. vulgaris. Indirect estimates of the AFLP mutation rate have shown values that vary from 10 −6 to 10 −5 (34)(35)(36), whereas the SSR mutation rate is higher; it ranges from 10 −3 to 10 −4 using both indirect (34,37,38) and direct (39, 40) estimates. Thus, following the model proposed in the work by Nei et al (41) that described the effects of a bottleneck on the genetic diversity of a population at a neutral locus, the work by Rossi et al (13) suggested the occurrence of a bottleneck in the Andes before domestication.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the lack of concordance between AFLPs and SSRs points to some ambiguity in the pattern, which cannot be resolved using the available data. Possible reasons include the differing discriminating power of the two marker types (for example, high proportions of null alleles in SSRs lower discrimination power), or different responses to environmental selection (AFLPs are more likely to be linked to loci under selection owing to random coverage of a genome; Gaudeul et al, 2004). The distribution of clusters does not overlap with any evident ecological factor, apart from distance from a nearby lake (Mukrz).…”
Section: Discussionmentioning
confidence: 99%